2022
DOI: 10.3390/biomedicines10020396
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Shock Wave Plus Intravesical Instillation of Botulinum Toxin A for Interstitial Cystitis/Bladder Pain Syndrome: Pathophysiology and Preliminary Result of a Novel Minimally Invasive Treatment

Abstract: Low-energy shock wave (LESW) therapy is known to facilitate tissue regeneration with analgesic and anti-inflammatory effects. LESW treatment has been demonstrated to be effective in treating chronic prostatitis and pelvic pain syndrome as well as overactive bladder, and it has a potential effect on interstitial cystitis/bladder pain syndrome (IC/BPS) in humans. LESW reduces pain behavior, downregulates nerve growth factor expression, and suppresses bladder overactivity by decreasing the expression of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 109 publications
(134 reference statements)
0
10
1
Order By: Relevance
“…Immature angiogenesis, leading to fragile vessels and potential areas of ischemia, has previously been reported in IC/BPS and is linked to an increase in VEGF expression [ 21 , 39 ]. Previous research has suggested that increased VEGF expression in IC/BPS might be caused by hypoxia in the bladder [ 55 , 56 ], but our data did not show evidence of hypoxia in WAS rats. This might indicate that NGF-induced mast cell activation plays a more prominent role in the increased release of VEGF [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Immature angiogenesis, leading to fragile vessels and potential areas of ischemia, has previously been reported in IC/BPS and is linked to an increase in VEGF expression [ 21 , 39 ]. Previous research has suggested that increased VEGF expression in IC/BPS might be caused by hypoxia in the bladder [ 55 , 56 ], but our data did not show evidence of hypoxia in WAS rats. This might indicate that NGF-induced mast cell activation plays a more prominent role in the increased release of VEGF [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These results provide evidence for the future treatment and safety of this novel treatment modality for patients with IC/BPS using LESW plus Botox instillation without bladder injection under anesthesia injection [32].…”
Section: Perspectives Of Future Research On Botox Treatment Ic/bps: U...mentioning
confidence: 68%
“…A prior immunohistochemistry study revealed the presence of cleaved SNAP-25 protein in the IC bladder suburothelium, suggesting that Botox molecules could be carried across the urothelial cell membrane with the assistance of LESW. These results provide evidence of the efficacy and safety of this novel treatment using LESW plus Botox instillation without anesthesia or bladder injection [ 32 ].…”
Section: Clinical Application Of Botox On Oab: Efficacy Adherence Adv...mentioning
confidence: 93%
See 2 more Smart Citations